Entwicklung und Zukunft der EU - Agrarhandelspraf̈erenzen fur̈ die sud̈lichen und os̈tlichen Mittelmeeranrainerstaaten - Harald Grethe; Stephan Nolte; Stefan Tangermann (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2005)
– The EU has recently completed negotiating a series of association agreements with mediterranean countries. Trade preferences for agricultural goods which are granted under these agreements as well as under former arrangements are analyzed by calculating the value of preference margins at several stages in the evolution of preferences. The total value of preference margins for all countries covered was about EURO 130 million under the agreements in the mid-seventies and increased by 48 per cent until 1995. It was eroded by about 14 per cent until 2000 due to the reduction of EU MFN tariffs. The extended preferences under the new agreements more than compensate for this erosion of preferences and result in a total value of preference margins of EURO 226 million once all agreements have entered into force.
Keywords: 330; Handelspräferenzen; Agraraußenhandel; EU-Staaten; Mittelmeerraum